Analisis Kepentingan Thailand dalam Kerjasama Proyek Pembangunan High Speed Railway (HSR) dengan Tiongkok - AM, Masrurotul Kamalia; Prasodjo, Haryo; Prinanda, Devita (Papua Journal of Diplomacy and International Relations, 2023)
This study aims to analyze Thailand's interest in the High Speed Railway (HRS) project. With the technique of analysis of the Nation-State, this paper explains Thailand's interests in cooperation with China by using neo-realism theory and explanative methods.  Thailand is working with China to build a high-speed rail with a distance of 873 kilometers. This High Speed Railway project is included in the Belt and Road Initiative with the Thailand-Laos-China route. There are several interests in this HSR cooperation; 1) in the economic sector that can stabilize the country's economy of Thailand and can increase foreign investment, 2) in the field of inter-regional cooperation, 3) in infrastructure development and modernization of development towards the main Geopolitical country. This cooperation also has a major impact among ASEAN countries, including making relations between neighbors closer and the basis for this cooperation is in accordance with Thailand's national interests. It is important because this HSR includes all the interests desired by Thailand in the welfare of its country. KEYWORDS High Speed Railway; Thailand; Tiongkok; Thailand’s Interest